2017
DOI: 10.1007/s00590-017-1931-y
|View full text |Cite
|
Sign up to set email alerts
|

Blood metal ion concentrations in metal-on-metal total hip arthroplasty

Abstract: We considered that cup version angle is one of the factors that have the greatest effect on blood metal ion concentration, and the target cup version angle that did not induce an increase in blood metal ion concentrations was approximately 20°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In our series, Co level and Co/Cr ratio were significantly higher in THA compared to RHA. These findings suggest an additional source of ion production in THA other than the head-cup bearing interface [ 4 , 38 , 39 ]. A similar result was described by Ridon et al and Johnson et al in series comparing RHA and THA constructs performed with the same acetabular component [ 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series, Co level and Co/Cr ratio were significantly higher in THA compared to RHA. These findings suggest an additional source of ion production in THA other than the head-cup bearing interface [ 4 , 38 , 39 ]. A similar result was described by Ridon et al and Johnson et al in series comparing RHA and THA constructs performed with the same acetabular component [ 15 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…MoM bearing surfaces were postulated at that time to decrease the risk of aseptic loosening related to wear and therefore to increase implant survivorship compared to conventional metal or ceramic on polyethylene bearings [1]. However, several reports in the literature raised safety concerns about MoM bearing due to increased chromium (Cr) and cobalt (Co) blood ion concentrations [2][3][4][5], adverse reaction to metal debris (ARMD) [6][7][8], osteolysis [9], and implant loosening [10][11][12][13], leading to restriction of use imposed by regulatory agencies worldwide. To date, the outcome of MoM THA is known to be poorer than conventional bearings with complication rates as high as 15.5% at ten years [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[128][129][130] Strong evidence indicated high average Co concentrations in the urine of patients who had undergone THA. 81,92,[131][132][133][134][135][136][137][138][139] An experiment administering Co intravenously in humans demonstrated that 40% was eliminated within the first 24 hours, 70% within a week, 80% within a month, and 90% within a year. 140 The geometric mean Mo level in the blood was 15.36 nmol/L, while the highest level in urine was 58.41 μmol/L.…”
Section: Excretion and Eliminationmentioning
confidence: 99%
“…Biochemical molecules, such as Ca 2+ , Mg 2+ , Zn 2+ , vitamin D (VD), and parathyroid hormone (PTH), are crucial components of bone marrow microenvironment, which may in uence the bone marrow osseointegration and the outcome of THA [6]. In addition, human bone marrow cells contain two populations of bone marrow stem cells: mesenchymal stem cells (MSCs also called bone marrow stromal cells) and hematopoietic stem cells (HSCs).…”
Section: Introductionmentioning
confidence: 99%